2012
DOI: 10.5846/stxb201109051304
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change on growth and yield of winter wheat in the semi-humid region of the Loess Plateau

Abstract: Impacts of climate change on growth and yield of winter wheat in the semi鄄humid region of the Loess Plateau. Acta Ecologica Sinica,2012,32(16) :5154鄄5163.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies have shown that climate change has shifted the sowing period of warm-temperatureloving crops such as maize and cotton earlier, with maize sowing 2 days earlier (34) and cotton sowing 5-12 days earlier (35). But winter wheat sowing is delayed by 2-3d/10a, and consequently the overwintering period is shortened by 5-6d/10a, and the full fertility period is shortened by 7-8d/10a (36). In general, the current climate change trend is favorable for warm-temperatureloving crops in the Northwest, but the safety threshold and long-term uncertainty still require further research.…”
Section: Crop Phenology and Suitabilitymentioning
confidence: 99%
“…Studies have shown that climate change has shifted the sowing period of warm-temperatureloving crops such as maize and cotton earlier, with maize sowing 2 days earlier (34) and cotton sowing 5-12 days earlier (35). But winter wheat sowing is delayed by 2-3d/10a, and consequently the overwintering period is shortened by 5-6d/10a, and the full fertility period is shortened by 7-8d/10a (36). In general, the current climate change trend is favorable for warm-temperatureloving crops in the Northwest, but the safety threshold and long-term uncertainty still require further research.…”
Section: Crop Phenology and Suitabilitymentioning
confidence: 99%